The lex mitior-principle and the chilean Constitutional Court - Bascuñán Rodríguez, Antonio (Revista de Estudios de la Justicia, 2015)
The article examines the constitutional status of the lex mitior-principle (retroactive application of the milder criminal law). This review provides a frame work for the analysis of a judgment of the Chilean Constitutional Court regarding a case arised by the application of a saving provision of the reform of chilean Bankruptcy law. The problema examined is the determination of the margin of legislative discretion left by the constitutional entrenchment of the principle.